Corporate Culture and Employee Identity: Cooption or Commitment through Contestation? - Price, Christine; Whiteley, Alma (Henry Stewart Publications, 2014)
Existing studies provide limited perspectives on consequences of corporate attempts to co-opt employees' identities and gain their commitment to management-espoused, values-based culture change, especially when employees perceive that managers are not living the required values. We conducted a grounded, empirical study within the Australian financial sector and explored employees' narrated experiences of living through a strategic cultural change programme, one which fostered strong social identification with the organization. Employees' informal folkloric activities privately validated (or otherwise) the corporate values through management's enactment of them: a derived and interpretative process we describe as employee ‘received practice’. When employees negatively experienced critical incidents, they had no legitimate avenue for contested meaning-making activities to resolve their concern; there was no available ‘negotiated practice’. Employee disengagement, diminished commitment and loss of discretionary energy resulted. Contributing to theory building, this paper presents ‘commitment through contestation’ as a sustainable, co-created corporate culture process. We propose that design of a conducive and situated environment, which validates folkloric discourse and includes employees in controversial dialogue within a relationship of mutuality, may foster sustainable cultural change by the addressing of value-threatening events and by allowing reaffirmation of both employee identification and their conditional commitment to the organization.